Sustainable Tourism through Coffee: Agrotourism Development in Turekisa Village, East Nusa Tenggara - Nono, Elfridus Andi Loke; Patiung, Markus; Sastryawanto, Hary (PT. Sangadji Media Publishing, 2024)
Agrotourism in Indonesia stands as a vital potential for development support. Indonesia boasts numerous agrotourism destinations, with one such developed site located in Turekisa Village, Ngada Regency, East Nusa Tenggara (NTT). This tourist destination has gained prominence due to its breathtaking natural beauty, often dubbed as the